Strategic Management in the Era of Disruptive Technologies: A Framework for Adoption and Implementation - Muhammad Arif Rahman; Forme Onray Siallagan (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
The relentless advancement of disruptive technologies necessitates a reevaluation of strategic management approaches within organizations. This research presents a comprehensive framework tailored for the adoption and effective implementation of disruptive technologies. Through an extensive review of literature and case studies, the framework integrates key elements such as environmental scanning, organizational readiness assessment, technology assessment, strategic alignment, and change management strategies. It emphasizes the importance of proactive adaptation and agile response to technological disruptions to maintain competitiveness and sustain growth. The proposed framework offers guidance to executives, managers, and decision-makers in navigating the complexities of technological innovation while mitigating risks and leveraging opportunities. By embracing this framework, organizations can enhance their ability to harness disruptive technologies, driving transformative change, and achieving strategic objectives in today's dynamic business landscape.